1989
DOI: 10.1111/j.1651-2227.1989.tb10879.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Reinforces Laryngeal Reflex Bradycardia in Infants

Abstract: The laryngeal chemoreflex involves bradycardia, apnea, swallowing and peripheral vasoconstriction. This reflex was studied in twelve infants, aged 5 days-28 weeks, who had sustained an apparent life-threatening event or were siblings of infants who had died of the sudden infant death syndrome. The bradycardic and apneic components of the reflex were found to be significantly, and sometimes powerfully, reinforced when elicited by pharyngeal water instillation during acute, mild hypoxia (transcutaneous PO2 4.6-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…from laryngeal stimulation, may lead to severe bradycardia. An augmentation of this reflex interaction has been shown in infants who subsequentl y died of SIDS (47). Similar augmentation of reflex brad ycardia has experimentally been produced by stimulation of the chemoreceptors with nicotine (15).…”
Section: • •mentioning
confidence: 65%
“…from laryngeal stimulation, may lead to severe bradycardia. An augmentation of this reflex interaction has been shown in infants who subsequentl y died of SIDS (47). Similar augmentation of reflex brad ycardia has experimentally been produced by stimulation of the chemoreceptors with nicotine (15).…”
Section: • •mentioning
confidence: 65%
“…sympathetic activation, increased alertness, and augmented peripheral chemoreceptor and baroreceptor sensory discharge. The clinical importance of these escape and defense mechanisms are supported by observations that infants who are at risk for life-threatening events are also less able to recover from LCR-induced reflex apnea and bradycardia (5,6) In this study, we tested the hypothesis that long-term postnatal exposure to nicotine attenuates and prolongs recovery from apnea and bradycardia in response to LCR stimulation. This notion was based on our previous observations that postnatal nicotine exposure leads to an attenuation of cardiorespiratory defense mechanisms to hypoxia (7).…”
mentioning
confidence: 91%
“…Others have shown that acute hypoxemia preceding laryngeal stimulation results in a reinforced cardiorespiratory response that may be fatal (2,5). They postulated that this combination may be a possible mechanism for SIDS.…”
Section: Table 3 Use Ofmeclzanical Ventilmentioning
confidence: 99%
“…CB denervation significantly increased the apnea response after laryngeal stimulation in 2-to 4-wk-old lambs, but this response remained unchanged in younger lambs, suggesting that a mature CB function plays a role in limiting reflex apnea caused by laryngeal water stimulation (14). However, it has been postulated that acute hypoxia preceding apnea induces a positive feedback that reinforces suppression of breathing, a mechanism that may play a role in the etiology of SIDS (2,5,20). Recently, there has been much interest in the study of peripheral chemoreceptor function in infancy because of a possible relationship between hypoxic exposure, CB malfunction, and the SIDS (2 1-23).…”
mentioning
confidence: 99%